Evaluation of physicians' approaches for the management of patients with diabetes during Ramadan in Iraq. (January 2023) - Alabbood, Majid; Alameri, Rafid; Alsaffar, Yasameen
Abstract: Background/objectives: In Diabetes Mellitus, fasting Ramadan comes with several challenges for both patients and physicians. However, majority of Muslims with type 2 diabetes fast Ramadan. Therefore, several guidelines have been developed to help physicians in managing their patients during Ramadan. This survey aims to investigate approaches adopted by Iraqi physicians for the management of diabetes during Ramadan. Design and methods: This was a cross-sectional online survey based study conducted via Google forms from March 20 through March 27, 2021. The participants were specialist doctors from different regions in Iraq who were directly involved in management of people with diabetes mellitus. The Google form was distributed to the intended specialist doctors through an invitation link via emails and WhatsApp groups exclusive for specialist doctors from Iraq. The survey was completely anonymous and participants' confidentiality was maintained throughout the study. A total of 140 responses collected in this study. Results: Majority of the participants were family physicians followed by internal medicine physicians and endocrinologists in the following rates 29.2 %, 27.1 % and 16.4 % respectively. Among the respondents, 94.3% reported giving advice to their patients regarding Ramadan fasting; 84.3% of this advice was based on several factors. Those who do not follow a specific guideline in their provision of care and depend on their experience represent 53%. Of them, family physicians were the predominant (70.2%). Pre-Ramadan education is provided by 75% of the participants. Minority (14.3%) allow patients with type 1 diabetes to fast Ramadan and 32.1% allow those with type 2 diabetes on insulin to fast. Recent diabetic ketoacidosis and recent severe hypoglycemia were the main causes for not allowing people to fast Ramadan, 79.3% and 74.3% respectively. Regarding treatment modification during fasting, 56.4 % of physicians change the frequency of administration. Lastly, 67.8 % scored 7/10 or above in the questions to test the familiarity of physicians with the established international guidelines. Conclusions: This survey highlights the importance of medical education for doctors and the need for structural education programs directed to the family physicians, internists, and other treating physician regarding the current practical guidelines. Health care providers need to be familiar with current diabetes and Ramadan fasting guidelines.